Menggelorakan makna energik sebagai brandscape erigo melalui iklan fireflies - Kurniawan, Febryan; Isnaini, Muhammad; Marta, Rustono Farady (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
Local brands in Indonesia today are growing and competitive and in this competition, various appropriate marketing communication strategies are needed, where this is needed to build attention from potential consumers. One of the local brands from Indonesia is Erigo, a company that has recently been discussed by internet users because one of its marketing strategies is to place advertisements in Time Square, New York. Advertising is one of the digital marketing strategies that serves to attract the attention of potential consumers through information on products and services offered to stick in the minds of consumers. Through a qualitative approach with an interpretive paradigm using Laura R. Oswald's marketing semiotics method, it was found that through the short advertisement